2016
DOI: 10.3390/nu8100544
|View full text |Cite
|
Sign up to set email alerts
|

A Trypsin Inhibitor from Tamarind Reduces Food Intake and Improves Inflammatory Status in Rats with Metabolic Syndrome Regardless of Weight Loss

Abstract: Trypsin inhibitors are studied in a variety of models for their anti-obesity and anti-inflammatory bioactive properties. Our group has previously demonstrated the satietogenic effect of tamarind seed trypsin inhibitors (TTI) in eutrophic mouse models and anti-inflammatory effects of other trypsin inhibitors. In this study, we evaluated TTI effect upon satiety, biochemical and inflammatory parameters in an experimental model of metabolic syndrome (MetS). Three groups of n = 5 male Wistar rats with obesity-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
72
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(91 citation statements)
references
References 61 publications
10
72
0
9
Order By: Relevance
“…The methodology was established in the Laboratory of Chemistry and Function of Bioactive Proteins (LQFPB) at Federal University of Rio Grande do Norte State, Brazil, and adapted by Carvalho et al [29]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The methodology was established in the Laboratory of Chemistry and Function of Bioactive Proteins (LQFPB) at Federal University of Rio Grande do Norte State, Brazil, and adapted by Carvalho et al [29]. …”
Section: Methodsmentioning
confidence: 99%
“…Recent research by our group demonstrated that an isolated trypsin inhibitor from Tamarindus indica L. seed (TTI) presents anti-obesity and anti-inflammatory activities [28, 29]. Ribeiro et al [28] analyzed the influence of TTI in an experimental model of satiety and found that the inhibitor was able to reduce food intake and weight gain of eutrophic animals, possibly by raising plasma CCK.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ribeiro et al; 21 Serguiz et al; 22 Lima et al; 23 Carvalho et al 24 também isolaram inibidores de tripsina do partido da F2.…”
Section: Figuraunclassified
“…18 Porém, quanto aos inibidores enzimáticos, tem-se observado um potencial terapêutico em sua utilização heteróloga para o tratamento de alguns estados de doença. [19][20][21][22][23][24] Embora os inibidores de tripsina estejam presentes naturalmente no reino vegetal, nas sementes de chia não existe relato na literatura sobre tal presença. Além disso, é importante investigar se esses inibidores comuns em sementes, também se apresentam e se mantêm nos seus produtos, como na farinha.…”
Section: Introductionunclassified